Advanced Requests for MAID: Are They Compatible with Canadian Medical Practice? - Mellett, James; Mack, Cheryl; Leier, Brendan (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
The recent passing of Bill C-7 has placed Advance Requests for MAID (ARMs) on Canada’s legislative agenda. We discuss how ARMs may create ethical and practical challenges for Canadian medical practice.